1988
DOI: 10.1007/bf01745965
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical heterogeneity of dermal mast cells in athymic and normal rats

Abstract: Mucosal mast cells (MMC) and connective tissue mast cells (CTMC) of the rat contain different proteoglycans, which can be distinguished using histochemical methods. The chondroitin sulphate proteoglycan of the MMC, unlike the heparin of the CTMC, does not show fluorescent berberine binding, is susceptible to aldehyde fixatives and stains preferentially with Alcian Blue in a staining sequence with Safranin. The majority of the dermal mast cells are typical CTMC and are located in the deep part of the dermis. Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…16,17) In rodents, there are two types of mast cells, connective tissue type mast cells (CTMCs) and mucosal mast cells (MMCs). 18) These two types of cells differ not only in tissue distribution but also in pattern of mediator production. In rat airway, CTMCs and MMCs are observed in the submucosal region and epithelial layer, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…16,17) In rodents, there are two types of mast cells, connective tissue type mast cells (CTMCs) and mucosal mast cells (MMCs). 18) These two types of cells differ not only in tissue distribution but also in pattern of mediator production. In rat airway, CTMCs and MMCs are observed in the submucosal region and epithelial layer, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In situ histochemical analysis of the proteoglycans of the subepidermal CTMC has thus shown that they con tain a heparin proteoglycan which is different from that of the MMC [Aldenborg and Enerback, 1986],…”
Section: Discussionmentioning
confidence: 99%
“…These cells, like the MMC, appear to contain little histamine, stain with alcian blue in a staining sequence with safranin, and show a cationic dye-binding which is susceptible to blocking by formaldehyde [Aldenborg and Enerback, 1986].…”
Section: Introductionmentioning
confidence: 99%
“…0018-2214/90 $03.00 +.12 9 1990 Chapman and Hall Ltd. their staining to nitrous acid and variation of ionic strength (Enerback, 1987). However, these techniques also reveal a finer degree of heterogeneity in heparincontaining mast cells in both rodents and man (Marshall et al, 1987;Aldenborg & Enerback, 1988).…”
Section: Introductionmentioning
confidence: 99%